THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON RETURN ON EQUITY IN PT. HUTAMA KARYA PERSERO TBK - Rujalil Rujalil; Kartin Aprianti (LPPM - STIE SAKTI ALAM KERINCI, 2021)
This study aims to determine and analyze the effect of Current Ratio and Debt to Equity Ratio on Return on Equity at PT. Hutama Karya Persero, Tbk either partially or simultaneously. The research sample for 10 years starting from 2010 -2019 used a sampling technique, namely purposive sampling. The population in this study is in the form of financial report data from 2006 to 2019 (annual financial reports available on the hutamakarya.com website which are listed on the IDX). The results showed that there was no partial and simultaneous effect of Current Ratio and Debt to Equity Ratio on Return on Equity at PT. Hutama by Persero Tbk.